DETERMINATION OF THE OPTIMAL METHOD OF INFLUENCE TO INCREASE THE EFFICIENCY OF RESERVOIR EXPLORATION - SEIDOV, Vagif; AGHAYEVA, Maleyka (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Even though the layers that make up oil and gas fields have different geological properties and, as well as different exploitation regimes applied in drilled wells, in most cases it is not possible to extract the expected volume of oil. To increase production, it is necessary to apply various physical effects to the layers. If the influence method is effective, it is possible to extract a certain amount of additional hydrocarbon from the layer. For this reason, selecting an effective influence method is considered to be one of the most important issues in the oil industry. Many factors influence the decrease in oil production at the field, one of which is the presence of high-molecular components. These components form pseudocrystalline plug in the pores of the rock and clog them. The article substantiates the effectiveness of using ultrasonic waves to clean rock pores from pseudocrystalline plug formed by highmolecular components (asphaltenes, resins). It determines the limiting values of ultrasonic vibration frequencies. There was selection, justification, and determination of limiting values characterizing an effective method of action for cleaning rock pores from pseudocrystalline plugs formed by high-molecular components during the development of oil and gas fields. The dependence of the influence of ultrasonic waves on the composition and density of fluids found in the pores of the rock, on the density of the rock, as well as on the liquid column settled in the well is established.Methods. It is recommended that ultrasonic waves be used to destroy pseudocrystalline plugs in the pores of the rock formed by high-molecular components found in heavy oil during the development of oil and gas fields.Results: as a result of the studies, it became known that for 1 m near the well, seismic waves with a frequency of 287 Hz should be used. For 10 m – 28.7 Hz; 100 m – 2.87 Hz; 200 m – 1.44 Hz; 300 m – 0.98 Hz; 400 m – 0.71 Hz; 500 m – 0.53 Hz. For an acoustic wave: from 0.33 to 525 Hz.Conclusions. Selection of rational methods of influencing the formations, an acceptable method of influencing the formation when the flow rate of wells in the development of fields decreases or completely stops and to justify the effectiveness of the choice.
Keywords: development; layers; pores; influence methods; ultrasonic waves